DESENVOLVIMENTO, CARACTERIZAÇÃO E LIBERAÇÃO IN VITRO DE COMPLEXOS DE INCLUSÃO NISTATINA:β-CICLODEXTRINA OBTIDOS POR DIFERENTES MÉTODOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
Purpose: This study prepared inclusion complexes (IC) between nystatin (Nys) and β-cyclodextrin (βCD), for posterior incorporation into a soft liner denture material, aiming to promote controlled release and a prolonged antifungal effect. Material and methods: Suspensions of Nys:βCD in molar ratios of 1:0.125, 1:0.25, 1:0.5, 1:0.625, 1:1, 1:2, and 1:4 were prepared in triplicate in distilled water, stirred for 24 h, and evaluated regarding phase solubility. The 1:1 and 1:2 molar ratios were selected to obtain IC using the following methods: physical mixture (PM), freeze-drying (FD), and spray-drying (SP). PM was homogeneous blended in a mortar for 15 min. The other IC were dissolved in water/ethanol solution (50:50 v/v), stirred for 24 h, and then submitted to one of the drying methods FD or SP. Drug, βCD, and IC were submitted to the following physicochemical characterization: field emission electron gun microscopy (FEG), Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), thermogravimetry (TGA), X ray diffraction (DXR), and nuclear magnetic resonance (NMR). For the in vitro dissolution study, 1:1 FD and SP IC were selected. Previously, a calibration curve of Nys in Milli-Q® water was plotted.The dissolution was made in triplicate using paddle device at 37ºC and 75 rpm during 8 h for Nys and 24 h for IC. The results were evaluated in relation to dissolution profile, efficiency (ANOVA-1 way) and kinetics. Results: Nys presented crystalline morphology and βCD presented more amorphous characteristics in comparison to the drug. PM and FD and SP IC presented more amorphous characteristics with small crystals. FT-IR analysis showed several shifts, reduction in intensity, and peak narrowing in the IC in relation to the non-complexed drugs. DSC analysis showed reduction in intensity of the fusion point peak of Nys in the IC, indicating partial complexation. DXR analysis showed peak size reduction and disappearance of spectral lines (“amorphization”), with SP showing more significant changes. It was proved that Nys was partially included into the βCD cavity in 1:1 FD IC, because a great chemical shift was observed for H5’, which is within the toroidal cavity of the oligosaccharide. Despite there was no statistically significant difference (p=0.1931) among the results of dissolution efficiency at 8 h, the 1:1 FD and SP IC showed an immediate release mechanics of the drug, with the 1:1 FD IC presenting the faster dissolution profile. The Nys and 1:1 FD and SP IC revealed the better kinetic adjustment for the biexponential model. Conclusion: Based on the results obtained by the characterization techniques, it was concluded that nystatin better complexed with β-cyclodextrin in 1:1 molar ratio in FD and SP methods. Freeze-drying inclusion complex 1:1 nystatin:β-cyclodextrin presented the better dissolution profile and biexponential kinetics, and this may result in interesting strategy to the development of pharmaceutical compounds that enable a controlled release when they are incorporated to the soft liner denture material.
Development, characterization, and in vitro release of nystatin:β- cyclodextrin inclusion complexes obtained using different methods
Keywords: estomatite sob prótese; Nistatina; solubilidade; liofilização; caracterização química; denture stomatitis; nystatin; solubility; freeze drying; chemical characterization; CNPQ::CIENCIAS DA SAUDE::FARMACIA